Physiological and histological effects of (zinc and iron) oxide nanoparticles on some fertility parameters in female mice - Shaima R. Ibraheem; Muntaha R. Ibrahim (Al-Mustansiriyah Journal of Science)
Nowadays nanoparticles have widespread application in various industries because of their special and unique features, there are many studies in side effects of nanomaterial. This study done by 40 white female mice with every other day intraperitoneally injection of low and high doses of both of ZnO kg of body weight) and FeO nanoparticles (5 and 40 mg/kg). After a 15 days period, the mice were sacrificed and blood samples were collected for hormone analysis, and tissue samples for morphometric studies. Statistical Analysis shows significant differences in LH, Estrogen, Progesterone hormone levels between groups, while there are insignificant differences in Follicle stimulating hormone (FSH) level between the groups compared with its level in the control group. The results also show that the highest level of LH reach 7.2 mIU/ml in the groups treated with low dose of zinc oxide, the highest level of FSH reach 4.58 mIU/ml in the groups treated with low dose of zinc oxide, the highest level of Estrogen hormone reach 69.5 ng/ml in the groups treated with low of dose zinc oxide and the highest level of Progesterone reach 1.9 ng/ml in the groups treated with high dose iron oxide. We conclude from the results that the low doses of ZnO has benefits in increasing fertility through high level of reproductive hormones, while the high levels of nanoparticles reduce fertility and there is a relation between FeO nanoparticles and progesterone levels which may need more future studies. Morphometric study of the ovary show increase in Follicular stages number range in the group treated with Low dose ZnO in compare with its range in the control groups. The lower range was belong to the group treated with the high dose of FeO. No significant differences has been found in the diameter mean of the different follicular phases between the group treated with low dose of ZnO NPs in compared with the control group. High dose of ZnO NPs cause significant increase in the diameter mean of Primordial follicles in compared with the control group. Low and high dose FeO NPs treated groups show significant reduction in the diameter mean of the different follicular phases in compared with the control group.